Analisis Loyalitas Pelanggan Ditinjau dari Aspek Kualitas Pelayanan, Citra Perusahaan dan Kepuasan Pelanggan - Bambang Irawan; Agus Purbo Widodo; Aloysius Jondar (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study involved 59 respondents who were representatives of PT Solusi Energy Nusantara service users. The purpose of this study was to determine the effect of Service Quality, Corporate Image and Customer Satisfaction on Customer Loyalty both partially and simultaneously. The research method used a quantitative approach consisting of research instrument testing, descriptive statistical analysis, multiple linear analysis, classical assumption testing, and hypothesis testing. The results of the study indicate that there is a positive and significant effect of the Service Quality variable on the Customer Loyalty variable. There is a positive and significant effect of the Corporate Image variable on the Customer Loyalty variable. There is a positive and significant effect of the Customer Satisfaction variable on the Employee Performance variable. There is a positive and significant simultaneous effect of the Service Quality, Corporate Image, and Customer Satisfaction variables on Customer Loyalty. The simultaneous determination value shows that the variation in changes in Customer Loyalty is influenced by Service Quality, Corporate Image, and Customer Satisfaction by 71.2%.